The Poles in Norway – we wanted workers but people arrived (Economic and Political Thought, 2016)
Former expectations related to free movement of people within the EEAcan be, at least partially, in question. The article aims at highlighting basictrends in migration outflows of Poles to Norway, with special attention paid tothe integration challenges, and in particular the integration of Polish childrenin Norway. Increasingly, more Poles decide on a more permanent settlementinstead of shuttling between Norway and Poland. It is a challenge not onlyfor them but also for the Norwegian society and policy in particular. Thearticle is a result of the TRANSFAM project, funded by the Norway Grants,which is focused on studying transnational migrations and starting familiesby Poles in Norway. The project participants are the Jagiellonian University(leader) and its partners from the Polish-Norwegian consortium: the Centrefor International Relations, Agder Research and Nova.